INFLUENCE OF RAMAYANA ON EATING HABITS AMONG INDIANS - Ms. Shama A Chavan (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2025)
The Ramayana, an epic deeply embedded in Indian culture, significantly influences the eating habits of many Indians. This epic narrates the story of Lord Rama, who is often depicted as upholding a sattvic diet, believed to promote purity and serenity. Sattvic food includes vegetables, fruits, whole grains, nuts, and dairy products, aligning with the principles of Ayurveda that recommend such a diet for mental and physical well-being. Many Indian households follow these dietary norms, especially during religious festivals and rituals. Vegetarianism, prevalent among various Indian communities, also finds roots in the Ramayana, reinforcing ideals of non-violence and respect for all living beings. It’s a reflection of Lord Rama's own dietary choices during his exile, where he subsisted on fruits and roots. Festivals like Diwali and Navratri, inspired by the Ramayana's significant events, see a rise in the consumption of traditional foods that align with Lord Rama's diet. For instance, foods like kheer, puri, and simple vegetable curries are prepared, mimicking the simplicity of meals during Rama’s time. Thus, the Ramayana not only serves as a spiritual guide but also subtly shapes dietary choices, encouraging a lifestyle that blends spiritual and physical nourishment.